UPAYA MENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK PADA TEMA 4 SUBTEMA 1 KELAS III SDN 067240 MEDAN - Dona Eby Ghail Meliala; Sri Wahyuni; HJ.Khoiriah (STKIP Subang, 2024)
This research aims to improve the thematic learning outcomes of class III students at SD Negeri 067240 Medan using the talking stick learning model. The form of this research is classroom action research (PTK) using quantitative research using experimental methods. The research results found that student learning outcomes showed only 44% completion and these results were not satisfactory. Student learning outcomes in cycle I with an average score obtained was 73.8 with a student completion level of 61% and this was said to be quite good. Student learning outcomes in cycle II obtained an average score of 81.6 with a completion percentage level of 83% which can be said to be very good. The results of the research conducted show that student learning outcomes have increased significantly by using the talking stick learning model.